The Influence of Non-Physical Work Environment and Self-Awareness on Employee Performance in the Riau Province Transportation Service - Febelani Anastasha; Nenny Anggraini; Desideria Regina (Universitas Kristen Indonesia, 2024)
Employee performance is defined as the amount and quality of work that an employee can accomplish while performing his primary responsibilities and functions in line with the tasks assigned to them. By applying a basic random sampling technique, 30 office workers were selected as the study's sample. The non-physical work environment variable (X1) has a significant level of 0.639 > 0.05 in the study, which indicates that the non-physical work environment variable affects employee performance at the Riau Province Transportation Office, but not significantly. The self-awareness variable (X2) yielded significant results with a significant level of 0.002 < 0.05, which shows that there is a significant influence of self-awareness on employee performance at the Riau Province Transportation Agency. Based on the simultaneous test results, the significant value is 0.000 <0.05 and the coefficient of determination R2 is 73.7%, indicating that the non-physical work environment and self-awareness have a significant influence on employee performance together, and other variables not included in this study have an influence on 24.5% of the data. The findings of this study suggest that in order to maintain improved employee performance, institutions should focus on the non-physical work environment and employee self-awareness. Keywords: Non-Physical Work Environment, Self-Awareness, Employee Performance